Traditional production landscapes for sustainable development mainstreaming agricultural biodiversity in East Java Indonesia - Permata Ika Hidayati (Jurusan Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2021)
Mainstreaming biodiversity in production landscapes ensures conservation and sustainable use of agricultural biodiversity. Mainstreaming integrates biodiversity in existing or new programs and policies, both cross-sectoral and sector-specific. The conventional model of agricultural production with limited diversity in production systems and use of high chemical input has taught us a valuable lesson as it is adversely impacting the environment, the essential ecosystem services, the soil health and the long term sustainability of our food systems. Using a qualitative participant observation approach, our study investigated four distinct traditional East Java production landscapes to gage (i) the farming communities’ response to institutional policies, programs and agricultural biodiversity-related activities in traditional East Java production landscapes and (ii) opportunities and challenges for sustainable development in smallholder traditional East Java farming systems. Results indicate that the top-down decision-making regime is the least effective towards achieving sustainable development in traditional East Java farming landscapes and that farmers’ experiential knowledge on participatory biodiversity management, maintenance and use for sustainable development are of critical importance to East Java’s agriculture and economy. Reclaiming agriculture’s spiritual roots through organic farming and locally grown food emerged as key, including the need for designing and implementing a more sovereign food system. Revisiting traditional smallholder farming under the COVID-19 pandemic and lessons learned for repurposing East Java’s agricultural policy are also highlighted.